Eleven New Triterpenoid Glycosides from the Roots of Ilex asprella. Issue 7 (12th June 2019) - Huang, Xiao‐Jun; Wen, Si; Guan, Xi‐Feng; Wu, Zhen‐Long; Li, Man‐Mei; Fan, Chun‐Lin; Zhang, Qing‐Wen; Chan, Ging; Wang, Ying; Ye, Wen‐Cai
Abstract: Asprellosides A‐K, nine new ursane‐type triterpenoid glycosides (1 –9 ), and two new oleanane‐type triterpenoid glycosides (10 and11 ), including six rare sulfated triterpenoid glycosides, were isolated from the roots of Ilex asprella . Their structures were determined on the basis of comprehensive spectroscopic analysis and chemical methods. Among these compounds, asprelloside B (2 ) and asprelloside C (3 ) are the first examples of triterpenoid glycosides bearing a rare 3, 4‐ O ‐disulfo‐xylopyranosyl residue. All the saponins isolated showed no significant effects against respiratory syncytial virus (RSV) and lipopolysaccharide‐induced nitric oxide production in Raw264.7 macrophages. Abstract :